(untitled) (Revista cientifica In Vestigium Ire, 2016)
This article deals with the study of the textile industry in the municipality of Samacá, Boyaca Colombia, understood as production process of socio-economic development of the region during the period comprised between 1884 and 1936. This article is then based on the theoretical and conceptual contributions of different economic schools, which currently contribute, in studies of business history. In this sense, the objective of the research is to recognize the significant role played by the textile industry in the region, from different temporal and spatial perspectives, with divergent analytical and methodological frameworks. Likewise, he was taken into account that the beginning of industrialization in Colombia, came with the incursion of two major sectors: steel and textiles Therefore, this research is inclined to make a significant recognition of the textile industry in the municipality of Samacá to establish its connection to theories and concepts of business economics, in its administrative and productive organization